Crack healing in nanocrystalline palladium. (September 2016) - Xu, Guoqiang; Demkowicz, Michael J.
Abstract: We present molecular dynamics simulations that demonstrate crack healing induced by external mechanical loading in three-dimensional models of nanocrystalline palladium. This behavior is due to the interaction of a crack with internal stresses in the surrounding microstructure. Our observations illustrate the importance of accounting for microstructurally-induced internal stresses when predicting the behavior of nano-scale cracks under mechanical loading. They also motivate further work to determine whether internal damage in hard matter may be mitigated by designing microstructures that heal cracks during mechanical loading.